2012
DOI: 10.1007/s11948-012-9406-3
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Engineering Ethics using BLOCKS Game

Abstract: The aim of this study was to investigate the use of a newly developed design game called BLOCKS to stimulate awareness of ethical responsibilities amongst engineering students. The design game was played by seventeen teams of chemical engineering students, with each team having to arrange pieces of colored paper to produce two letters each. Before the end of the game, additional constraints were introduced to the teams such that they faced similar ambiguity in the technical facts that the engineers involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…To set the context for this study, we begin with a broad discussion of ethics education� We then focus on what ethics looks like in engineering education to better understand how lecture and game-based instruction are leveraged in this study� Next, we will consider "games" throughout the literature and an examination of what other studies have found when using games in the engineering ethics space� In Western culture, many undergraduate universities and colleges offer philosophy courses focused on teaching philosophical ethics� These courses provide a theoretical background of topics such as virtue ethics, feminist ethics, and consequentialist ethics, among others (Paulson & Kretz, 2018)� As Callahan (1980 explains, such courses should be included in undergraduate curriculum because "morality is part of any reflective personal life, and because ethical perspectives and specific moral rules are part of any cultural and civic life… ethical problems are inescapable…it is difficult to think of any aspect of personal or public life that will not be determined or conditioned by moral values" (p� 62)� For students, such courses, at the very least, can provide clear evidence that there are ethical problems in all aspects of life, and how one understands and responds to these problems can make a difference in the lives of others, both positively and negatively (Callahan, 1980)� Ethics education at this stage is appropriate because ethical problems can happen at any time in a person's life and are also a part of jobs and professions (Callahan, 1980)� For this reason, not only do we see introductory philosophy/ethics education as important in undergraduate studies, but also as an integral part of many different disciplines' education� Some examples of these fields include counseling (Lamb, 1991), psychology (Plante & Pistoresi, 2017), and medicine (Wong et al�, 2022)� Engineering is yet another example of a field heavily intertwined with ethics, especially with the reach of its many branches including chemical, civil, electrical, industrial, mechanical, and so on� Considering a slice of ethics education, via the engineering discipline, may help improve ethics and engineering education broadly� History shows us what can happen when ethical problems are encountered but poorly attended to, such as with the case Challenger disaster in 1986 where seven space shuttle members died due to known flaws in the spacecraft ("Space Shuttle Challenger Disaster", n�d�)� But in engineering there is still a "disconnect between the ethics education of contemporary engineering students…and the ethics realities of contemporary engineering practice" (McGinn, 2018, p� 3)� Some students and educators may even consider ethics as a simple box to check off rather than an essential part of the engineering design process (Lloyd & van de Poel, 2008)� To help curb these deficiencies some institutions have turned to game-based learning for their engineering ethics education, with Barab and Dede (2007) noting that, over the past few decades, game-based learning methodologies emerged as a type of curricula in science education� Lau et al� (2012) provided one example of game implementation in the engineering classroom� In this study, students were tasked with creating a design using colored paper in accordance with a list of constraints� Each group of students was set up with roles and ...…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To set the context for this study, we begin with a broad discussion of ethics education� We then focus on what ethics looks like in engineering education to better understand how lecture and game-based instruction are leveraged in this study� Next, we will consider "games" throughout the literature and an examination of what other studies have found when using games in the engineering ethics space� In Western culture, many undergraduate universities and colleges offer philosophy courses focused on teaching philosophical ethics� These courses provide a theoretical background of topics such as virtue ethics, feminist ethics, and consequentialist ethics, among others (Paulson & Kretz, 2018)� As Callahan (1980 explains, such courses should be included in undergraduate curriculum because "morality is part of any reflective personal life, and because ethical perspectives and specific moral rules are part of any cultural and civic life… ethical problems are inescapable…it is difficult to think of any aspect of personal or public life that will not be determined or conditioned by moral values" (p� 62)� For students, such courses, at the very least, can provide clear evidence that there are ethical problems in all aspects of life, and how one understands and responds to these problems can make a difference in the lives of others, both positively and negatively (Callahan, 1980)� Ethics education at this stage is appropriate because ethical problems can happen at any time in a person's life and are also a part of jobs and professions (Callahan, 1980)� For this reason, not only do we see introductory philosophy/ethics education as important in undergraduate studies, but also as an integral part of many different disciplines' education� Some examples of these fields include counseling (Lamb, 1991), psychology (Plante & Pistoresi, 2017), and medicine (Wong et al�, 2022)� Engineering is yet another example of a field heavily intertwined with ethics, especially with the reach of its many branches including chemical, civil, electrical, industrial, mechanical, and so on� Considering a slice of ethics education, via the engineering discipline, may help improve ethics and engineering education broadly� History shows us what can happen when ethical problems are encountered but poorly attended to, such as with the case Challenger disaster in 1986 where seven space shuttle members died due to known flaws in the spacecraft ("Space Shuttle Challenger Disaster", n�d�)� But in engineering there is still a "disconnect between the ethics education of contemporary engineering students…and the ethics realities of contemporary engineering practice" (McGinn, 2018, p� 3)� Some students and educators may even consider ethics as a simple box to check off rather than an essential part of the engineering design process (Lloyd & van de Poel, 2008)� To help curb these deficiencies some institutions have turned to game-based learning for their engineering ethics education, with Barab and Dede (2007) noting that, over the past few decades, game-based learning methodologies emerged as a type of curricula in science education� Lau et al� (2012) provided one example of game implementation in the engineering classroom� In this study, students were tasked with creating a design using colored paper in accordance with a list of constraints� Each group of students was set up with roles and ...…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Challenger disaster case study is also often used in traditional engineering ethics instruction during lectures� Some methods used in this teaching format include providing students with "do's and don'ts" lists related to ethical engineering practice, having students use basic scenarios to apply said principles, and the use of case studies where students must analyze and provide an approach for resolving the case (Alfred & Chung, 2012)� The latter is the most effective approach used in classroom lectures (Whitbeck, 1996, as cited in Alfred & Chung, 2012, but Drew (2011) described how engineering courses taught through lectures often fail to interest students, leading to reduced engagement and shallow learning� Therefore, other approaches, like games, have been introduced to increase the usefulness and engagement of engineering ethics instruction� The example above describes Lau et al�'s (2012) study as implementing a "game," but there are additional terms with more distinct meanings used in education� Games, gamification, and game-based learning are terms that are frequently used interchangeably in educational settings� While there is some disagreement on exact definitions, Plass (2017) differentiated between them� Specifically, game-based learning is distinct in that the original learning task is transformed into a game with a design grounded in discipline-specific applications (Plass, 2017)� Bodnar et al� (2016 went into further detail, defining gamification as "the application of game design elements to nongame scenarios" (p�148)� A common and simple form of gamification is the use of points, badges, and leaderboards where participants earn points for completing tasks (Bodnar et al�, 2016)� Further, they continued to explain that game-based learning has many benefits including that it provides immediate feedback, informs participants they are making progress, and motivates them (Bodnar et al�, 2016)� Bodnar et al�'s (2016) systematic review of the games meant to teach undergraduate engineering students, provided support for the conclusion that the implementation of games in undergraduate engineering classrooms improved student learning and attitudes� For this paper, we define game-based learning as it aligns with Plass (2017) and Shaffer et al� (2005) in that an original learning task has been transformed into a game with learning outcomes� In the original lecture-based instruction scenario at the study site, students would engage in discussions of historic engineering and philosophical ethics problems, with the learning task being that they would contribute to the discussion about, and listen to, the problems� For the larger National Science Foundation (NSF) study from which this paper is derived, three games were created to transform the role of the student in different ways, as an individual (1) voting on an ethical response to a problem, (2) choosing a potentially ethically dubious card option due to the nature of the situation, or (3) ordering other engineers' views on ethical responses to issues in the field� All these games stemmed from the same situated engineering ethics problems of the lecture, but had the player take on a role with richer context and details, more agency, and from a different perspective on the ethical problem, leading to the varied learning outcomes from each game� Slota and Young (2014) described the importance of implementing game-based learning beyond simply t...…”
Section: Literature Reviewmentioning
confidence: 99%
“…To help curb these deficiencies some institutions have turned to game-based learning for their engineering ethics education, with Barab and Dede (2007) noting that, over the past few decades, game-based learning methodologies emerged as a type of curricula in science education. Lau et al (2012) provided one example of game implementation in the engineering classroom. In this study, students were tasked with creating a design using colored paper in accordance with a list of constraints.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The different roles within each team were then pressured in different ways to either move forward with the product or halt it due to concerns regarding its ability to function properly. The scenario was created in such a way as to mimic the Challenger disaster and the decisions/ lack of communication that led to it (Lau et al, 2012). Between the implementation of the game and viewing of the real Challenger disaster video, students' opinions on the importance of ethical statements in engineering practice increased for all but one statement (Lau et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation